The Collapse of Argentine Science Under Javier Milei: One Year of Unprecedented Defunding - Debat, Humberto (Infonomy, 2025)
This article critically examines the systematic erosion of Argentina's public science ecosystem during the first year of President Javier Milei's administration, highlighting the broader implications for the nation’s socio-economic and geopolitical landscape. Drawing on prior forecasts of a decline in scientific support, I assess the immediate and long-term ramifications of the government's decision to defund key scientific institutions and initiatives. By reviewing recent reports and government actions, I argue that Milei's policies —characterized by devastating budget cuts exceeding 32% of R&D public investment, large-scale layoffs of researchers, and the suspension of critical projects— jeopardize Argentina’s status as a scientific leader in Latin America. These measures threaten to dismantle decades of progress in Argentina’s scientific community, undermining its capacity to drive innovation, address pressing national challenges, and maintain global research collaborations. Public science has long served as a pillar for technological development and social well-being, playing an irreplaceable role in confronting issues such as public health, agriculture, and climate change. In this context, I argue that Milei's approach not only weakens Argentina’s scientific foundations but also jeopardizes its capacity for sustainable, autonomous growth. Unless immediate policy reversals are enacted, these actions will exacerbate existing social inequalities, accelerate the exodus of intellectual talent, and inflict long-lasting damage on Argentina’s capacity for self-determined development, ultimately isolating the country from vital global scientific networks.
Keywords: Argentine; Scientific system; Scientific policy; Javier Milei; Public science ecosystem; Government; Public Administration; Scientific support; Budget cuts; Long lasting effects